Pengaruh Label Halal dan Tanggal Kadaluarsa Terhadap Keputusan Pembelian Produk Sidomuncul - Ahmad Ulil Albab Al Umar; Muammar Taufiqi Lutfi Mustofa; Dessy Fitria; Alfia Miftakhul Jannah; Yusvita Nena Arinta (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
The halal industry is very developed lately. The halal lifestyle that is currently trending in Indonesia consists of the Islamic financial sector, halal food, halal travel, halal clothing, halal recreation, and halal media, halal medicines, halal medical care (hospital), and halal cosmetics. For example, a pharmaceutical industry such as Sidomuncul. Sidomuncul is a company that has the most halal products at this time. This study aims to partially examine the effect of the halal label and the expiration date on purchasing decisions. Then simultaneously analyze the effect of the halal label and the expiration date on Sidomuncul purchasing decisions. This research is quantitative descriptive research. The method in this research uses multiple linear regression with SPSS 25. The population in this study are all people who buy Sidomuncul products, while the sample in this study was determined by 50 respondents. The results of this study resulted in a significant t-test value of 0,000, which means partially the halal label has a significant effect on purchasing decisions, the expiration date resulted in a significant t-test value of 0,006, which means partially expiration date has a significant effect on the Sidomuncul product purchase decision, and simultaneously the halal label and expiration date affect the Sidomuncul product purchase decision.